Anger and Stress Management Techniques for Successful Educational Leadership - Osias Kit T. Kilag; Jackelyn B.Yamson; Manilyn T. Bocao; Nelson A. Cordova Jr; John Michael Sasan (International Journal of Scientific Multidisciplinary Research, 2023)
This study aimed to investigate the effectiveness of an anger and stress management intervention program on school leaders' burnout, stress, anger, and leadership skills. The study utilized a pre-test, post-test, and follow-up design and collected quantitative data using standardized measures. The study also collected qualitative data through focus group discussions with school leaders at the end of the intervention phase. The data were analyzed using descriptive statistics, paired-sample t-tests, repeated-measures ANOVA, and thematic analysis. The quantitative results showed significant improvements in burnout, stress, anger, and leadership skills among the school leaders who participated in the intervention program. The qualitative findings revealed four main themes: increased self-awareness and emotional regulation, improved communication and conflict resolution skills, enhanced problem-solving and decision-making skills, and improved work-life balance and well-being. The study suggests that anger and stress management interventions can be effective in improving school leaders' well-being and leadership skills. These findings have practical implications for educational institutions and policymakers to implement anger and stress management interventions to support the well-being of school leaders and improve the quality of education